Erythropoietin‐mediated protection in kidney transplantation: nonerythropoietic EPO derivatives improve function without increasing risk of cardiovascular events. (22nd August 2013) - van, Willem G.; van, Harry; Ploeg, Rutger J.; Leuvenink, Henri G. D.
Summary The protective, nonerythropoietic effects of erythropoietin (EPO) have become evident in preclinical models in renal ischaemia/reperfusion injury and kidney transplantation. However, four recently published clinical trials using high‐dose EPO treatment following renal transplantation did not reveal any protective effect for short‐term renal function and even reported an increased risk of thrombosis. This review focusses on the current status of protective pathways mediated by EPO, the safety concerns using high EPO dosage and discusses the discrepancies between pre‐clinical and clinical studies. The protective effects are mediated by binding of EPO to a heteromeric receptor complex consisting of two β‐common receptors and two EPO receptors. An important role for the activation of endothelial nitric oxide synthase is proposed. EPO‐mediated cytoprotection still has enormous potential. However, only nonerythropoietic EPO derivatives may induce protection without increasing the risk of cardiovascular events. In preclinical models, nonerythropoietic EPO derivatives, such as carbamoylated EPO and ARA290, have been tested. These EPO derivatives improve renal function and do not affect erythropoiesis. Therefore, nonerythropoietic EPO derivatives may be able to render EPO‐mediated cytoprotection useful and beneficial for clinical transplantation.